Utilization of Generic Cardiovascular Drugs in Medicare's Part D Program. Issue 2 (December 2021) - Ma, Iris; Tisdale, Rebecca L.; Vail, Daniel; Heidenreich, Paul A.; Sandhu, Alexander T.
Abstract : Background: Generic medications cost less than brand-name medications and are similarly effective, but brand-name medications are still prescribed. We evaluated patterns in generic cardiovascular medication fills and estimated the potential cost savings with increased substitution of generic for brand-name medications. Methods: This was a cross-sectional study of cardiovascular therapies using the Medicare Part D database of prescription medications in 2017. We evaluated drug fill patterns for therapies with available brand-name and generic options. We determined the generic substitution ratio and estimated the potential savings with increased generic substitution at the national, state, and clinician level. We compared states with laws related to mandatory pharmacist generic substitution and patient consent for substitution. Results: Of ≈22.9 billion spent on cardiovascular drugs in Medicare Part D prescription programs in 2017, ≈11.0 billion was spent on medications with both brand-name and generic options. Although only 2.4% of medication fills were for the brand-name choice, they made up 21.2% of total spending. Accounting for estimated brand-name rebates, generic substitution for these medications would save 641 million, including 135 million in costs shouldered by patients. Furthermore, the minority of clinicians with the lowest generic utilization was responsible for a large proportion of the potential cost savings. Conclusions: There are substantial potential cost savings from substituting brand-name medications with generic medications. These savings would be primarily driven by lower use of brand-name therapies by the minority of clinicians who prescribe them at increased rates. Abstract : Supplemental Digital Content is available in the text.